Water Resources Mapping for Firefighters in Kotamadya Yogyakarta Based on Android - Indrianingsih, Yuliani; Sajati, Haruno; Sugara, Bayu (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2019)
Fire extinguishing system in placing reservoirs there are still many officers who do not know the location so that they can implement computerized technology so that firefighters can work to maximize the information technology made by the author well. Mobile-based reservoir mapping system application developed using Geofence method. The main purpose for this application that officers can easily find the location of the reservoir closest to the location of the fire and where officers can also find out the location of the reservoir distance from the fire. The accuracy of testing results with Google maps where the accuracy is very precise to the location of the water source or reservoir. Testing using a smartphone comparison from Android 4.1 Jelly Bean version to Android 7.0 Nougat can run with distance results in the application using google maps, get the same results and where there is a test version of Android V4.4 Kitkat that did not work because RAM does not support this application. Testing in the form of a black box method where this method tests every function contained and the test is functioning and running as smoothly as possible where the system is functioning properly with success rate 100%.